Perancangan Sistem Informasi Penggajian Pegawai Berbasis Java di Sekolah Menengah Kejuruan Nusantara Wisata Respati - Meri Chrismes Aruan; Luh Putu Widya Adnyani (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
The development and progress of IT-based information technology is very rapidly developing and has a very important role. Information systems are a necessity for agencies to utilize information as a basis for data administration and processing. To meet these needs, the agency conducts activities related to computer-based information systems as a tool to increase employee creativity. This system is designed to handle the transaction of escort and payment salary calculations and can guarantee validiity, complete authorization, classification of assessments, timeliness of each payroll transaction. In the Middle School Nusantara Wisata Respati Middle School still uses a manual payroll system, which is Microsoft Excel, so that people who are not authorized to enter and view data and can change the impact will disrupt the activity in processing salary data. For this reason, it is necessary to design a Java-based payroll information system at the Respati Archipelago Tourism Middle School.